Benefits of Activity-Based Interventions Among Female Adolescents Who Are Overweight and Obese - Bonney, E.; Ferguson, G.; Burgess, T.; Smits-Engelsman, B. (Pediatric Physical Therapy, 2019)
Purpose: The purpose of this study was to compare the effects of 2 activity-based motor interventions among female adolescents who are overweight and obese. Methods: This study was conducted in a low-income community of Cape Town, South Africa. The study involved 52 participants classified as overweight and obese. Participants were randomly assigned to task-oriented functional training or Wii Fit intervention. Both interventions were 45 minutes of active training once a week for 14 weeks. Outcome measures included aerobic fitness, motor coordination, and self-efficacy. Data were collected before and after the interventions. Results: Participants in both groups demonstrated significant improvement in aerobic fitness and motor coordination but not self-efficacy. However, no between-group differences were observed on any of the outcomes. Conclusions: Activity-based interventions may improve aerobic fitness and motor coordination in female adolescents who are overweight and obese and may also help prevent declines in physical fitness and coordination in this population.
Research Article
Keywords: Adolescents; Overweight; Obese; physical fitness